Evaluasi Kinerja Sistem Drainase Berdasarkan Analisis Sedimentasi Di Jalan Makmur Hutan, Medan Tembung - Oktavianus Napitu; Muhammad Al Bukhary; Rizky Simanjuntak; Wisnu Prayogo; Rumilla Harahap (CV. SINAR HOWUHOWU, 2026)
Urban drainage systems frequently experience performance degradation due to sedimentation and increased domestic wastewater, leading to inundation in residential areas. This study aims to evaluate the causes of inundation and sedimentation in the drainage system on Jalan Makmur Hutan, Medan Tembung District, Medan City. Primary data were obtained from seven observation segments through direct field measurements, including channel dimensions and sediment thickness, while secondary data consisted of 11-year rainfall records (2013–2023) from the Deli Serdang Climatology Station and population data for the same period. Hydrological analysis was conducted using the Log Pearson Type III distribution method to estimate design flood discharges for various return periods, and population projections for 2, 5, 10, 25, and 100 years were calculated using arithmetic, geometric, exponential, linear regression, and least square methods to estimate domestic wastewater discharge. The results showed that the average sediment thickness reached 0.27 m, reducing channel capacity by 29.7%, while the 5-year return period flood discharge was 6.34 m³/s. These findings indicate that sedimentation is the primary factor contributing to reduced drainage performance and frequent inundation in the study area. Therefore, regular channel normalization, routine maintenance, and integrated domestic wastewater management are essential to improve drainage performance and prevent future flooding.